Evaluation of treatment access and scope of a multistate hepatitis C virus Extension for Community Healthcare Outcomes telehealth service in the US Indian Health System, 2017‐2021. Issue 2 (16th December 2022) - Wirth, Ashley N.; Cushman, Nicholas A.; Reilley, Brigg A.; Leston, Jessica D.; Mera, Jorge R.; Levander, Ximena A.; Stephens, David J.
Abstract: Purpose: American Indians/Alaska Native (AI/AN) persons are disproportionately affected by hepatitis C virus (HCV). The Northwest Portland Area Indian Health Board Indian Country Extension for Community Healthcare Outcomes (ECHO) telehealth clinic supports primary care providers (PCPs) in treating HCV. We evaluated the extent to which Indian Country ECHO increases access to HCV treatment and holistically serves AI/AN patients. Methods: We conducted a retrospective descriptive analysis of Indian Country ECHO treatment recommendations from 2017 to 2021. Recommendations were classified into the following categories: HCV treatment with direct‐acting antiviral medication, prevention, substance use disorder treatment, lab or imaging orders, pharmacological considerations, behavior changes, other, and referral. Subanalysis of treatment recommendations was completed for patients with cirrhosis. Findings: Of the 776 patients from 77 Indian Health System facilities who presented at Indian Country ECHO, 718 (93%) received treatment recommendations. Most patients (93%) received recommendations for HCV treatment by their PCP; only 3% received a recommendation for referral to a hepatologist or liver transplant center for additional care. Most patients received at least 1 recommendation beyond the scope of HCV treatment provision. Cirrhosis criteria were met by 8% of patients, of which 80% received recommendations for HCV treatment by their PCP and 25% received recommendations for referral to a specialist for additional care. Conclusions: Most patients presented at the Indian Country ECHO received recommendations for HCV treatment by their PCP, along with recommendations beyond the scope of HCV. Indian Country ECHO telehealth clinic provides comprehensive recommendations to effectively integrate evidence‐based HCV treatment with holistic care at the primary care level.